Proposals for Annual Plan 1965-66 Memoranda and Sector wise Descriptive Notes Government of Gujarat - Planning Commission (Planning Commission, 1965)
Thus in financial terms, the five-year target of Rs. 236.50 crores is likely to be exceeded by an amount of about Rs. 11.37 crores. In fact the excess requirement under different subheads of development works up to about Rs. 33 crores which is partly offset by savings of the order of about Rs. 22 crores in the remaining sub-heads of development.
Government of Gujarat, General Administration Department